IMPLEMENTASI PENDIDIKAN INKLUSI DALAM MENINGKATKAN KETERLIBATAN AKADEMIK SISWA REGULER DAN SISWA BERKEBUTUHAN KHUSUS - Yoseptry, Ricky; Nurlianti, Nurlianti; Minah, Minah; Permata, Destia Dewi; Syarofah, Lailis (STKIP PGRI Situbondo, 2025)
This study aims to describe the implementation of inclusive education at SDN Jembatan Besi 01 Pagi. This study uses a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and document studies. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. Students with special needs have different backgrounds, with some being more comfortable interacting with fellow students with special needs, while others interact well with regular students. Social interactions in inclusive classes involve associative patterns such as cooperation in academics and non-academically, accommodation provides motivation and assistance so that students with special needs are more open and integrated with regular students. The involvement of parents and communities and the formation of a school culture that supports inclusion and respects diversity are also crucial.